The effects of regular exercise on the number of osteoclasts in ovariectomized Sprague dawley rat mandibles - Rini Maya Puspita; Fitrina Rachmadanty Siregar (Biomedical Engineering, 2014)
Objective: This study aimed to examine the effect of regular exercise on the number of osteoclasts in ovariectomized Sprague Dawley rat mandibles.Methods: Eight female Sprague Dawley rats, 3 months of age, were ovariectomized and divided into control (untreated) and treatment group (regular exercise). The exercise conducted by the rats ran on a specially designed rat treadmill for 12 weeks, 5 times per week, at a speed of 10-18 m/min for 60 minutes per day. At the end of the treatment, the mandible was taken and cleaned out from the tissue for making the histological preparations with Hematoxylin and Eosin (HE) stain. The number of osteoclasts counted from each histological preparation on 10 visual fields and the obtained data were analyzed using independent t-test.Result: The number of osteoclast was lower significantly in ovariectmized rats compared to control group (P < 0.001). Conclusion: Regular exercise can decrease the number of osteoclasts in ovariectomized Sprague Dawley rat mandibles.Key Words: mandibles; menopause; regular exercise; the number of osteoclasts;